1993
DOI: 10.1111/j.1432-1033.1993.tb17750.x
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of cytochrome P450RR1 from Rhodococcus rhodochrous

Abstract: A soluble cytochrome P450 whose synthesis is induced by and that binds 2-ethoxyphenol was purified to apparent homogeneity from Rhodococcus rhodochrous strain 116. The enzyme had a subunit molecular mass of 44.5 kDa as determined by SDSRAGE and a PI of 5.2. The electronic absorption spectrum indicates that the native cytochrome in the absence of substrate is predominantly in the low-spin state (13% high-spin state in 50 mM Mops, pH 7.0, 25°C). 2-Methoxyphenol binds to the cytochrome with a macroscopic dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 20 publications
1
45
0
Order By: Relevance
“…Third, we have identified enzymatic activities in the cell extracts that catalyze the ring cleavage of the expected products of the postulated O-dealkylation reactions. Finally, in an in vitro system consisting of purified P-450RR1 and chemical reductants, we have demonstrated that P-450RR1 catalyzes the O-dealkylation of 2-ethoxyphenol to produce catechol (10).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Third, we have identified enzymatic activities in the cell extracts that catalyze the ring cleavage of the expected products of the postulated O-dealkylation reactions. Finally, in an in vitro system consisting of purified P-450RR1 and chemical reductants, we have demonstrated that P-450RR1 catalyzes the O-dealkylation of 2-ethoxyphenol to produce catechol (10).…”
Section: Methodsmentioning
confidence: 99%
“…The presence of P-450 in extracts of cells grown on 4-ethoxybenzoate was confirmed by CO difference spectra. Coomassie blue staining of the lanes of the same In experiments performed with the purified cytochrome, it has been shown that P-450RR1 catalyzes the O-dealkylation of 2-ethoxyphenol and 2-methoxyphenol to form catechol (10). It was conjectured that P-450RR2 catalyzes the 0-dealkylation of 4-ethoxybenzoate and 4-methoxybenzoate, producingp-hydroxybenzoate.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…strain NI86/21. On the basis of the lack of N-terminal sequence homology, the 2-ethoxyphenolinduced cytochrome P-450 RR1 from Rhodococcus rhodochrous (18) and the enzyme of Rhodococcus sp. strain NI86/21 also appear not to be related.…”
Section: -[Sgnh]-x-[gd]-x-[rhpt]-x-c-[limvfap]-mentioning
confidence: 99%